An individualised curriculum to teach numeracy skills to children with autism: programme description and pilot data. Issue 4 (November 2014) - Tzanakaki, Pagona; Brown, Neil; Farmer, Kait; Fraser‐Smith, Jenny; McClatchey, Kirstie; McKeown, Vibeke; Sangster, Ali; Shaver, Isabel; Templeton, Jenny
<x xml:space="preserve">Abstract</x> Teaching mathematics to children with autism is an area with limited research evidence. In this study we developed a teaching manual based on Maths Recovery, a numeracy programme designed for typically developing children. Six children with autism participated in the study and received daily numeracy teaching over a 20‐week period. Our aims were to explore whether Maths Recovery can be used as a numeracy curriculum for children with autism and to evaluate the progress the children make after a period of intensive teaching. Using a pre‐test post‐test design we found that the adapted Maths Recovery numeracy curriculum was successfully incorporated within each child's individualised teaching programme, and that all six children improved their mathematical ability over the course of the intervention. Our data show promising results and support the rationale for larger evaluation studies.